Anatomic and pathological characterization of choroidal melanoma using multimodal imaging: what is practical, what is needed?. Issue 3 (June 2015) - Lindner, Tobias; Langner, Sönke; Falke, Karen; Walter, Uwe; Krüger, Paul-Christian; Pohlmann, Andreas; Zimpfer, Annette; Stahnke, Thomas; Hadlich, Stefan; Guthoff, Rudolf; Erbersdobler, Andreas; Niendorf, Thoralf; et al.
Abstract : Choroidal melanoma is the most frequently occurring intraocular tumor in adults. The aim of this work is to assess the potential of state-of-the art in-vivo and ex-vivo imaging modalities for the characterization of choroidal melanoma. Multimodal imaging of a choroidal melanoma was performed in a 53-year-old male patient. In-vivo ophthalmoscopy, ultrasound microscopy, duplex ultrasound, and 7.0 T MRI were performed. Ex-vivo examination of the enucleated eye included 7.0 and 9.4 T magnetic resonance microscopy as well as histopathology with hematoxylin and eosin staining. Imaging of choroidal melanoma with ultrahigh field MRI and duplex sonography provides detailed morphologic and functional information of the eye. High-spatial-resolution MRI at 9.4 T shows details of the internal texture of melanoma and other structures of the eye with an in-plane spatial resolution of 32 μm. Ultrahigh field in-vivo MRI at 7.0 T and ex-vivo MRI at 7.0 and 9.4 T correlate well with histologic evaluation. In-vivo ultrahigh field MRI is an emerging technique for the characterization and staging of ocular tumors. The combination of in-vivo ultrahigh-field MRI and duplex sonography has the potential to complement or even substitute complex and invasive biopsies.